2007
DOI: 10.2466/pms.104.4.1297-1309
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Upper Limb Proprioceptive Acuity

Abstract: Although upper limb movements are known to be slower and more variable in elderly persons, the extent to which these changes are associated with deficits in movement-related sensory feedback is poorly understood, despite the importance of proprioception in the control of skilled movement. Age-related changes were examined with 22 participants (10 of M age 27 years and 12 of M age 75 years) in performance of an elbow position-matching task which varied in terms of interhemispheric transfer and/or the need to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
61
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(74 citation statements)
references
References 43 publications
10
61
3
Order By: Relevance
“…In contrast to the ipsilateral matching condition, the magnitudes of matching errors were greater in older compared with young adults. Our findings are corroborated by other investigations of agerelated differences in proprioceptive ability between young and older individuals (Adamo et al 2007(Adamo et al , 2009Herter et al 2014). These results may be explained by deterioration of cognitive processes involved in sensorimotor function (Li and Lindenberger 2002) and reduced hemispheric connectivity caused by corpus callosum degeneration (Abe et al 2002).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In contrast to the ipsilateral matching condition, the magnitudes of matching errors were greater in older compared with young adults. Our findings are corroborated by other investigations of agerelated differences in proprioceptive ability between young and older individuals (Adamo et al 2007(Adamo et al , 2009Herter et al 2014). These results may be explained by deterioration of cognitive processes involved in sensorimotor function (Li and Lindenberger 2002) and reduced hemispheric connectivity caused by corpus callosum degeneration (Abe et al 2002).…”
Section: Discussionsupporting
confidence: 92%
“…These findings contrast with those reported by Adamo et al (2007Adamo et al ( , 2009, who found that older adults had significantly greater matching errors when replicating joint angles with the same and opposite arms. Methodological differences may account for conflicting findings, since Adamo et al (2007Adamo et al ( , 2009) conducted single-joint position matching tasks in a gravity-eliminated environment. In the present study, we used a multi-joint position matching task which allowed gravitational forces to influence arm movements.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…In [29], the slowing of fine motor performances in aging was quantified using timing measures during hand-related tasks. Other works were based on identifying the effect of aging on the grip force for holding and moving object [12], coordinated eye and hand movements [31], proprioceptive acuity [2], and activation of shoulder muscles during dynamic activities [11] involving pull, push, elevation, and throw. However, preparation of upper extremity movement is an important component that needs to be addressed.…”
Section: Related Workmentioning
confidence: 99%